GIS and conjunctive use for irrigated agriculture - Fredericks, J. W., author; Labadie, J. W., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
A microcomputer based geographic Information (GIS) Is presented for decision support in conjunctive use of groundwater and surface water for irrigated agriculture. A powerful, yet low-cost, raster GIS for PC's called IDRISI is utilized for preparing and processing grid-based spatial data for MODRSP, a modified version of the USGS 3D finite-difference groundwater model, MOD FLOW. Spatially distributed stream-aquifer response coefficients are generated and then used within a generalized river basin network model called MODSIM. The GIS is also used for displaying and analyzing results of conjunctive use schemes. Integration of GIS, MODFLOW, and MODSIM allows analysis of conjunctive use plans with consideration of decreed flow and storage rights, river calls, exchanges, trades, and plans for augmentation. The hydrologic components include: reservoir seepage, irrigation infiltration, groundwater pumping, channel losses, return flows, river depletion flows due to pumping, and aquifer storage. Capabilities of the decision support system are demonstrated on a 70 mile section of the Lower South Platte River, Colorado.
Irrigation and water resources in the 1990's
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.